THE ANTIOXIDANT STUDIES OF TWO MEDICINAL PLANTS, SPHAERANTHUS INDICUS AND HELIANTHUS ANNUS - Yugal Kishor Sarle (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Objective: The present study deals with the antioxidant assays of the different plant extracts of two medicinal plants, Sphaeranthus indicus and Helianthus annus. Methods: Dried leaves of S. indicus and H. annus were packed in separate round bottom flasks for sample extraction using ethanol, methanol, hexane, and distilled water as solvents for 72 h, and the extracts were collected after evaporating the solvents. Antioxidant studies of the various extracts were performed by 1-diphenyl-2-picrylhydrazyl and Ferric Reducing Ability of Plasma assays. Results: The IC50 value of S. indicus, H. annus and ascorbic acid was 87.25, 188.67, and 18.69 respectively in methanol extracts. In chloroform extracts IC50 value was 940.35 and 460.45 respectively. Among the two plants studied, S. indicus and Helianthus annus showed better 2-diphenyl-1-picryl-hydrazyl (DPPH), scavenging activity than H.annus with IC50 values. The FRAP assay results for both the plants indicated that the methanol fractions showed good results when compared with standards, ascorbic acid. These results clearly indicate that S. indicus methanol fraction had better antioxidant activity when compared to both standards. Conclusion: It is concluded that S. indicus and H. annus have excellent antioxidant activities which could be the major contributing factors for their medicinal roles. Further studies in this direction are being carried on.